Designing and Teaching of Language Independent Object Oriented Programming Course - Husain, Moula; Akki, Mallikarjun S.; Maralappanavar, Meena S.; Narayan, D. G. (Journal of Engineering Education Transformations, 2015)
Programming Languages play a crucial role in developing any software applications. Academicians and IT professionals give more priority for mastering many programming languages. Learning many language syntax and constructs will not contribute much in building problem solving skills. For any given task, students should be capable of solving it by using any of the programming languages. More importantly, students should build an art of optimizing the performance of the application by applying fundamental and advanced concepts of programming languages. In this paper, we propose an innovative way of designing and teaching of Object Oriented Programming Concepts without sticking to one particular language. In our first attempt, we practiced teaching of this course with two languages namely, C++ and Java. Our experimental results and students feedback prove the effectiveness of designing and teaching of Language independent Object Oriented Programming course. Moreover, it develops the skills of implementing and applying object oriented concepts using any object programming language.